2013
DOI: 10.1007/s00276-013-1098-0
|View full text |Cite
|
Sign up to set email alerts
|

The vascular basis of the hemi-hamate osteochondral free flap. Part 1: vascular anatomy and clinical correlation

Abstract: The hemi-hamate osteochondral flap has a reliable anatomical vascular basis, and is clinically feasible as a technique for early vascularisation of the osteochondral fragment to sustain the transferred articular cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Despite five of the eight cadavers demonstrating statistically significant changes in subluxation following biomechanical testing, the authors reported that the donor site morbidity was clinically minimal [4]. In fact, donor site morbidity after hemi-hamate arthroplasty appears low, however, tenderness and nerve tethering in the scar have been reported, and long-term investigations are scarce [10,[21][22][23]. Further, Sollaccio et al observed substantial variation in articular surface morphology of the dorsal distal hamate between and within individuals, and no uniform similarity in shape between the articular surface of the dorsal distal hamate and the volar middle phalanx base [11].…”
Section: Discussionmentioning
confidence: 99%
“…Despite five of the eight cadavers demonstrating statistically significant changes in subluxation following biomechanical testing, the authors reported that the donor site morbidity was clinically minimal [4]. In fact, donor site morbidity after hemi-hamate arthroplasty appears low, however, tenderness and nerve tethering in the scar have been reported, and long-term investigations are scarce [10,[21][22][23]. Further, Sollaccio et al observed substantial variation in articular surface morphology of the dorsal distal hamate between and within individuals, and no uniform similarity in shape between the articular surface of the dorsal distal hamate and the volar middle phalanx base [11].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the benefit of the vascularization of increasingly small grafts remains unclear. Technical success in vascularization of other small defects has been described, particularly in the setting of small osteochondral flaps, suggesting that outcome studies may be forthcoming [38][39][40]. Consideration of the benefits and risks remains important when grafting to defects of all lengths.…”
Section: Discussionmentioning
confidence: 99%
“…39 Overall complication rate was 35%, of which osteoarthritis is a major concern and reported as a radiological finding in up to 50% of the cases. 82,84,85 Possible reasons for this include denervation and poor vascularization, to which Rozen and colleagues 87 proposed a vascularized hemi-hamate free flap. Other complications include PIPJ joint contracture (present in up to 10% of patients) and graft resorption.…”
Section: Hemi-hamate Replacement Arthroplastymentioning
confidence: 99%